AN AUTHENTIC OVERVIEW OF THE EDUCATIONAL RIGHTS AND PROSPECTS OF MUSLIM WOMEN - Rimmi Datta; Jayanta Mete (UIN Sunan Gunung Djati Bandung, 2021)
Consciousness, knowledge, and understanding in Islam are a fundamental prerequisite for all Muslims to allow them to affirm, think, and behave under the principles of religion. Muslim women and girls have been seen for years as potential objects of modernization and modernity. Popular belief has arisen that, for a nation to be prosperous, girls need to be educated and will raise their nation from its broad range of social issues. Women's education was indispensable to the discourses that pursued to modernize emerging and Muslim societies. Muslim women thought it was just as important to educate girls as it was to educate boys, and that they acknowledged parental and marital influence over the rights of women to be educated and to work. As Muslim women move up the educational ladder, the role of religion as a predictor of academic achievement is dwindling. This emphasis on the experiences of educated Muslim women exacerbates the prevailing narrative of modernity that portrays women's education and gender equality as an expression of individual women's choice and free will against any patriarchal structures of family, culture, and Islam. Use qualitative approach This paper deals with the historical perspective of Muslim woman's education, their educational rights, curriculum development of Muslim education, and the importance of Muslim female education